Differences in Platelet Counts in K2edta Blood Samples with Varying Volumes Using a Hematology Analyzer - Alya Firda Mahfiroh; Uli Mas’uliyah Indarwati; Defi Nurul Hayati; Minto Rahaju (Proceedings Series on Health & Medical Sciences, 2026)
Background: Platelet count examination is an essential hematological test that requires proper anticoagulant usage to prevent blood coagulation. The accuracy of platelet measurement is influenced by the proportion of anticoagulant and blood volume. Method: This study used an observational cross-sectional design conducted at the Clinical Laboratory of Universitas Muhammadiyah Purwokerto. A total of 15 samples were obtained using purposive sampling. Platelet counts were measured using a hematology analyzer with three blood volume variations (0.5 mL, 1 mL, and 3 mL). Data were analyzed using normality tests and one-way ANOVA. Results: The mean platelet counts for 0.5 mL, 1 mL, and 3 mL samples were 23486.67, 24986.67, and 25206.67, respectively. Statistical analysis showed no significant difference (p = 0.375; p > 0.05). Conclusion: Variations in blood sample volume in K2EDTA tubes do not significantly affect platelet count results when measured using a hematology analyzer.